Questioning the Dominance of Native-English Teachers in ELT Profession - Tahan HJ Sihombing (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2022)
It is often assumed that native-English teachers are the best teachers in the teaching of English. This results in the preference towards native-English teachers and the isolation of non-native English teachers when it comes to English teaching profession. This assumption should not be perpetuated. English teaching researches have shown that native-English teachers are not always the ideal teachers in the teaching of English. The findings of the researches state that non-native English teachers have more advantages compared to the native ones especially in the context of English as an international language where English can no longer be associated with only English-speaking countries. This paper discusses the issue of the preference towards native-English teachers and the isolation of non-native English teachers.